Comparative Study of Training Effect Using Some Skill and Physical Tests on Young Soccer Players Aged (14 - 15) Years Old - Sajad Mohsen Ali; Naji Khadem Ali (College of Physical Education and Sport Sciences, 2021)
The importance of the research lies in physical fitness as an important component in soccer and the problem of the research lies in differences in training programs from one place to another and not benefiting from great countries experiences. The research aimed at making a comparative study on the effect of a training program used for a certain period of time as well as identifying differences between pre and post-tests. The researchers hypothesized significant statistical differences in test results in favor of posttests. The researcher used the experimental method for 45 days on Russian players aged (14- 15) years old. The researcher concluded significant statistical differences in posttests.